UNICONDYLAR KNEE ARTHROPLASTY — PROS AND CONS (LITERATURE REVIEW) - Baburkina, Olena; Ovchynnikov, Oleg; Bludova, Maryna; Zhygun, Anatoliy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
In the modern world, despite the increased availability of hightech orthopedic care, the number of patients with gonarthrosis does not decrease, and thanks to public awareness, more and more people turn to orthopedists for surgical help. Due to its high efficiency, the leading role in the treatment of terminal gonarthrosis has been firmly occupied by total knee arthroplasty for more than four decades. Unicondylar knee arthroplasty in patients with unilateral arthrosis allows to largely preserve physiological kinematics, to achieve minimal bone and soft tissue traumatization during surgery and, as a result, to obtain a higher functional result. The objective of the work is to analyze the data of the world literature regarding unicondylar knee arthroplasty, its advantages and disadvantages. Material and methods. The authors analyzed the publications devoted to single-condylar knee arthroplasty from the Google search engine, scientific and metric electronic databases PubMed, Medline and other relevant sources of scientific and medical information. Correct patient selection is vital to ensure a successful outcome with OEKS. The main indication for OEKS is deforming arthrosis of the II–III century. with a predominant lesion of the internal part of the knee joint and varus deformation of the lower limb or with a more pronounced pathology of the external part of the knee joint and valgus deformation of the lower limb. Results. The authors analyzed the literature sources on single-condylar endoprosthesis of the knee joint. Indications, contraindications, biomechanical features, type of endoprosthesis fixation, type of endoprosthesis platform, features of lateral gonarthrosis, and complications of single-condylar knee arthroplasty are determined. Conclusions. The analysis of selected literary sources showed that single-condylar arthroplasty of the knee joint is an effective means of preserving the bone. However, careful patient selection and precision of surgical technique remain the key to a successful outcome.